2022
DOI: 10.1186/s12873-022-00570-3
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison and outcomes of emergency department presentations with respiratory disorders among Australian indigenous and non-indigenous patients

Abstract: Background There is sparse evidence in the literature assessing emergency department presentation with respiratory disorders among Indigenous patients. The objective of this study was to evaluate the clinical characteristics and outcomes for Indigenous Australians in comparison to non-Indigenous patients presenting to Emergency Department (ED) with respiratory disorders. Methods In this study, two non-contiguous one-month study periods during wet (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Indigenous people have a higher burden of chronic health conditions, including cardiorespiratory disorders, giving rise to higher morbidity and mortality [33][34][35][36][37]. Understanding the different clinical manifestations [38][39][40] and appropriate interventions [41][42][43][44][45][46][47][48][49][50] will help in early diagnosis and management of chronic health conditions in the Indigenous population, for better health related outcomes. Varying manifestations of sex differences in PFTP's have been demonstrated in this study, both with and without underlying radiological evidence of CADs among an Indigenous Australian cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Indigenous people have a higher burden of chronic health conditions, including cardiorespiratory disorders, giving rise to higher morbidity and mortality [33][34][35][36][37]. Understanding the different clinical manifestations [38][39][40] and appropriate interventions [41][42][43][44][45][46][47][48][49][50] will help in early diagnosis and management of chronic health conditions in the Indigenous population, for better health related outcomes. Varying manifestations of sex differences in PFTP's have been demonstrated in this study, both with and without underlying radiological evidence of CADs among an Indigenous Australian cohort.…”
Section: Discussionmentioning
confidence: 99%
“…As such, it is plausible that the current study captured anywhere from 40% to 60% of current Indigenous COPD patients in the TEHS region. More recently, several aspects of respiratory health issues among Indigenous Australians from the TEHS region of the NT has been reported in the literature 19–24 28 32 35–40 52–66. Hence, this study could be considered as an important further step forward67 in addressing COPD disease awareness and knowledge in an Indigenous population.…”
Section: Discussionmentioning
confidence: 76%
“…In this study, SOB was the predominant reason for hospital presentation. A recent study also demonstrated that SOB was the most common reason for hospital presentation 28. Additionally, a higher proportion of Indigenous patients were transferred to tertiary care hospital from other remote/regional health centres 28.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations